Das landesweite Netzwerk ADAPTHERA: erste Ergebnisse einer flächendeckenden, krankenkassenübergreifenden und transsektoralen rheumatologischen Versorgung = The regional network ADAPTHERA : rheumatology care through coordinated cooperation: comprehensive, trans-sectoral, covering all health insurance ; initial results - Schwarting, Andreas; Ückert, Frank (Zeitschrift für Rheumatologie, 2016)
The aim of the rheumatology network ADAPTHERA (“risk-adapted rheumatology therapy“) is to achieve a comprehensive improvement in rheumatology care by coordinating treatment in a regional, trans-sectoral network. Accompanying biomedical research projects, training concepts, and the construction of a rheumatology register (gathering data and biomaterials) should furthermore ensure the stable and sustainable optimisation of care. In the pilot phase (2012-2015) the focus of the ADAPTHERA network, required as a “regional key project“ within the framework of the Initiative on Health Economy of Rheinland-Palatinate (RL-P), Germany, was placed on the optimisation of the early diagnosis of rheumatoid arthritis, where it is well-known that there is a significant care deficit.Through the intensive, stable, and coordinated cooperation of all health care partners in the field of rheumatology (registered general practitioners and orthopaedic specialists, registered core rheumatologists as well as the Association of Rheumatology of RL-P) a unique regional, comprehensive offer with verifiable care optimisation has been established in RL-P. The network is supported by outstanding collaboration with the Association of Statutory Health Insurance Physicians and the self-help organisation Rheumatology League.The aims that were established at the start of the project will be achieved by the end of the pilot phase:- significant improvement in the early diagnosis of rheumatoid arthritis (an average of 23.7 days until diagnosis by rheumatologists)- access covering all health insurance (regardless of the particular scheme the patients belong to)- comprehensive (verifiable participation of general practitioners from all over RL-P)- data and biomaterials collection, established as a basis for biomarker research, and a rheumatology register for RL-P.